2017
DOI: 10.1016/j.asieco.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

An impact evaluation of investment in infrastructure: The case of a railway connection in Uzbekistan

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…This is supported by the studies of Liu and Wang [26] and Wang et al [27] who also found that transport infrastructure imposes a spatial spillover effect on economic growth. Furthermore, Yoshino and Abidhadjaev [28] employed difference-in-difference estimation to examine the impact of railway construction connection on economic growth in Uzbekistan. Their findings show that a railway connection generates positive impact for the region as well as the distant parts of country.…”
Section: Transportation Infrastructurementioning
confidence: 99%
“…This is supported by the studies of Liu and Wang [26] and Wang et al [27] who also found that transport infrastructure imposes a spatial spillover effect on economic growth. Furthermore, Yoshino and Abidhadjaev [28] employed difference-in-difference estimation to examine the impact of railway construction connection on economic growth in Uzbekistan. Their findings show that a railway connection generates positive impact for the region as well as the distant parts of country.…”
Section: Transportation Infrastructurementioning
confidence: 99%
“…Another example of spillover effect demonstrates the impact of railways in Uzbekistan on economic growth using the difference-in-difference method (Yoshino and Abidhadjaev, 2017a). After the connectivity between the agricultural region and cities was completed, the growth rate of the economy increased by 2.2 percentage points compared with the region where no railway had been constructed (0.2 percentage points).…”
Section: Spillover Effectmentioning
confidence: 99%
“…The treatment is commonly identified through increased accessibility due to transport infrastructure improvements such as the opening of new road or rail connections. A variety of methods is applied in this field: Gibbons & Machin (2005) use Difference-in-Differences models with unique treatment and control groups, Ahlfeldt & Feddersen (2015) identify discontinuities in their data, Yoshino & Abidhadjaev (2017) work with several treatment groups subject to different treatments, and Gibbons et al (2019) estimate the effect of a continuous treatment intensity variable.…”
Section: Literature Reviewmentioning
confidence: 99%